Investigations on the control of the red scale Aonidiella aurantii (Mask.) and citrus thrips Scirtothrips aurantii faure on citrus in South Africa - Georgala, M. B (Stellenbosch : Stellenbosch University, 2012)
Dissertation (PhD (Agric)) -- University of Stellenbosch, 1977.